Abstract to publication conversion in pediatric critical care medicine in Pakistan - Anwarul Haque; Mohammad Shahzad; Humaira Jurair; Naveed Ur Rehman Siddiqui; Sidra Ishaque; Qalab Abbas (Acute and Critical Care, 2021)
Background To determine the rate of conversion of abstracts presented at conferences into full-text articles published in peer-reviewed journals in the field of pediatric critical care medicine (PCCM) in a developing country. Methods We retrospectively reviewed PCCM abstracts from Pakistan presented at national and international pediatric and critical care conferences over 10 years (January 2010 to March 2020). Data included abstract characteristics, such as presentation (poster/oral), presenter (fellow/resident), time of meeting (month and year), type of meeting, study design and topic; and publication characteristics, such as journal name, time (month and year) and first author. The primary outcome was publication rate of PCCM abstracts presented in meetings and time (months) from presentation to publication. Results A total of 79 PCCM abstracts were presented in 20 meetings during the study period. There were 65 poster presentations (82.28%), of which 63 (79.74%) were presented at international critical care conferences and all presenters were PCCM fellows. In total, 64 (81%) abstracts were descriptive observational studies (retrospective: 50, 63.29%) and prospective (14, 17.72%). Only one was an interventional randomized controlled trial. The publication rate of PCCM abstracts was 63.3% (50/79) and the mean time to publication was 12.39±13.61 months. The publication rate was significantly correlated to the year of publication (P<0.001). Conclusions The PCCM abstract publication rate and mean time from presentation to publication was 63.3% and 12.39±13.61 months, respectively, in a developing country.